Transmucosal Absorption Enhancers in the Drug Delivery Field - Sam Maher; Luca Casettari; Lisbeth Illum (Pharmaceutics, 2019)
Drug delivery systems that safely and consistently improve transport of poorly absorbed compounds across epithelial barriers are highly sought within the drug delivery field. The use of chemical permeation enhancers is one of the simplest and widely tested approaches to improve transmucosal permeability via oral, nasal, buccal, ocular and pulmonary routes. To date, only a small number of permeation enhancers have progressed to clinical trials, and only one product that includes a permeation enhancer has reached the pharmaceutical market. This editorial is an introduction to the special issue entitled Transmucosal Absorption Enhancers in the Drug Delivery Field (https://www.mdpi.com/journal/pharmaceutics/special_issues/transmucosal_absorption_enhancers). The guest editors outline the scope of the issue, reflect on the results and the conclusions of the 19 articles published in the issue and provide an outlook on the use of permeation enhancers in the drug delivery field.